The effect of service temperature on the impact strength and fracture toughness of GTD-111 superalloy. (September 2021) - Taheri, Morteza; Jam, Jafar Eskandari; Beni, Mohsen Heydari; Khorram, Ali; Kashani-Bozorg, Seyed Farshid; Torkamany, Mohammad Javad
Highlights: Microstructural studies confirmed that airfoil microstructural damage was greater than that of the root. The mechanism of airfoil damage was liquation and crack formation around the MC carbide, Cr-Mo boride and γ-γ′ eutectic after servicing. Due to the presence of brittle phases, including MC carbide, the mechanism of fracture in airfoil was cleavage. Abstract: The study of the impact resistance of gas turbine blades due to exposure to internal and external damage can prevent human and economic disasters. In this study, a GT 13-E2 General Electric gas turbine blade was used, which has been exposed to heating, hot gases, the material to a temperature of 850–900 °C in 10, 000 operating hours. Microstructural examinations of the two sections of the airfoil and the root confirmed the microstructural damage of the airfoil due to more severe working conditions. Impact test was performed at temperature 25 and 900 °C for both airfoil and root sections. Impact test results showed that the fracture toughness for blade root in both temperatures of 25 and 900 °C was 4.7 and 6.2 J, respectively. This value was 2.4 and 3.3 for the airfoil blade, respectively. This was the formation of hard phases that were formed during service in airfoil due to unwanted aging. These phases included M23 C6 carbide, γ′ nanometer particles and the TCP phase.